Electronic Coupling of Metal‐to‐Insulator Transitions in Nickelate‐Based Heterostructures - Lucia Varbaro; Bernat Mundet; Claribel Domínguez; Jennifer Fowlie; Alexandru B. Georgescu; Lukas Korosec; Duncan T.L. Alexander; Jean‐Marc Triscone (Advanced Electronic Materials, 2023)
Abstract In rare earth nickelates, the metal‐to‐insulator transition observed as a function of temperature can be described using an electronic and a structural order parameter. The electronic one is linked to the electronic disproportionation observed below the transition temperature and the structural one characterizes the breathing mode that develops in the low temperature phase. Here SmNiO3/NdNiO3 superlattices are grown with insulating LaAlO3 spacer layers to study the unusual coupling of metal‐to‐ insulator transitions observed at SmNiO3/NdNiO3 interfaces and determine the role of the two order parameters. Temperature‐dependent transport measurements reveal that a single unit cell of LaAlO3 inserted between SmNiO3 and NdNiO3 leads to a complete decoupling of the metal‐to‐insulator transitions suggesting that the order parameter controlling the coupling is the electronic one.